(untitled) (Chittagong University Journal of Biological Sciences, 2025)
This study is aimed to assess the water quality status of Dhanmondi Lake in a single term by the use of water quality index (WQI). Samples were collected from six sampling sites in the post-monsoon season; in situ and laboratory analysis were performed for water quality parameters like temperature, pH, EC, DO, BOD, TDS, Cl, SO4, HCO3, free CO2, total hardness, Turbidity, Ca, Mg, and heavy metals. WQI for all the six sampling sites were calculated using weighted arithmetic index method. Considering the water quality standards set globally (as proposed by WHO) and locally (as set by DPHE), the EC, TDS, pH, HCO3, Cl and SO4 contents of Dhanmondi Lake (180μS/cm, 115.20 mg/L, 7.8, 120.1 mg/L, 29.59 mg/L and 11.82 mg/L respectively) were within the permissible value, but DO, BOD5 and turbidity (4.26 mg/L, 24.04 mg/L and 11.05 NTU respectively) values were beyond unsatisfactory for aquatic environment. The water of the lake is found to be very poor in quality (WQI > 75) which indicates its unsuitability for its use in drinking and fisheries purposes. The water quality of the lake is required to be restored and public awareness should be raised as well. Chittagong Univ. J. B. Sci. Vol 13 (1&2): 31-39, 2025